Etnomatematika Pada Kebudayaan Suku Dayak Bentian Dalam Menumbuh Kembangkan Literasi Matematis - Nurdin Arifin; Eudia Fortuna (Sekolah Tinggi Teknologi Industri (STTI) Bontang, 2021)
Mathematical concepts are always useful in everyday life to solve problems at hand. Learning mathematics that is associated with the surrounding (contextual) circumstances, especially in the culture of an area, is expected to be able to improve the ability of students in learning. Learning mathematics which is associated with the culture of an area is called ethnomathematics. Moreover, the government is currently promoting literacy. Literacy in mathematics is called mathematical literacy/mathematical literacy is the knowledge to know and apply basic mathematics every day such as to communicate both orally and in writing, to reason, and to solve problems. This service is carried out through a zoom meeting application that is given to 6th semester students, as a preparation effort before students carry out the Introduction to Learning Environment (PLP) at school. This service method uses the ADDIE (Analyze, Design, Develop, Implementation, and Evaluation) model. In the results of this service, a discussion was held on the ethnomathematics of the Bentian Dayak tribe in relation to learning mathematics and participants were able to make mathematical literacy questions. In the end, participants will be able to apply ethnomathematics and mathematical literacy in learning